Criminal Liability for the Forgery of Marriage Requirements Documents in Indonesia's Positive Legal Perspective - Yoyok Adi Syahputra (AT-TAFAHUM: Journal of Law, 2026)
Forgery of marriage requirements documents is an act that not only disturbs the order of marriage administration, but also has the potential to cause legal consequences for the validity of the marriage as well as the rights and obligations of the parties. In practice, there are still various forms of identity forgery and administrative documents used as a condition for marriage registration, raising problems regarding the application of criminal liability to the perpetrators. This study aims to analyze the form of criminal liability for perpetrators of falsification of marriage requirement documents based on Indonesia's positive law and examine the problems of law enforcement. This research uses normative legal research methods with a statutory approach and a conceptual approach. Legal materials were obtained through literature studies which included primary, secondary, and tertiary legal materials, then analyzed qualitatively using descriptive-analytical methods. The results of the study show that falsification of marriage requirements documents can be held criminally liable if the elements of the crime are met, there is a mistake in the perpetrator, and no justification or forgiving reason is found. Law enforcement against these criminal acts still faces various obstacles, including differences in perception in distinguishing administrative violations and criminal acts, weak coordination between agencies, and the suboptimal system for verifying marriage administrative documents. Therefore, strengthening criminal accountability needs to be carried out through consistent application of the law, strengthening coordination between agencies, digitizing the marriage administration system, and increasing public legal awareness. These efforts are expected to provide legal certainty, protect the integrity of marriage administration, and prevent falsification of marriage requirements documents in Indonesia.